Penerapan Prosedur Terapi Bekam Basah Pada Pasien Hipertensi dengan Ansietas - Atika Jatimi; Paris Olwan; Yunita Amilia; Mukhlish Hidayat (Universitas Nazhatut Thullab Al- Muafa Sampang, 2022)
Introduction: Abnormal changes in systolic and diastolic blood pressure in hypertensive patients can trigger the emergence of anxiety. Anxiety can worsen conditions in hypertensive patients. Objective: The purpose of this study was to describe nursing care with the application of wet cupping therapy procedures to reduce anxiety in hypertensive patients. Methods: This research uses a descriptive case study method by analyzing in-depth an object of research whose unit of analysis is individual from assessment, diagnosis, intervention, implementation, and evaluation. The respondents were two people with a medical diagnosis of hypertension who were selected using a purposive sampling technique. Results: The results showed that on the fourth day P1 and P2 said they did not have difficulty sleeping, did not get dizzy, did not pace, and did not worry, supported by objective data, the patient did not appear restless, with the interpretation of the assessment problem resolved. Conclusion: After being given nursing care with the application of wet cupping therapy to 2 patients, it can be concluded that wet cupping therapy can reduce anxiety in hypertensive patients.